Xenophon und die spartanische Nauarchie - Lukas Thommen (Historika : Studi di Storia Greca e Romana, 2016)
Xenophon generally considered Sparta to have been a well organized, ideal city-state, which fact he attributed to the presumed lawgiver Lycurgus. By contrast, he saw the Sparta of his own time as having gone awry in several ways, especially due to the undertakings of leading Spartans towards other Greek cities, which lead to the corrupting influx of gold as a symbol of prestige (Lac. 14). These misguided Sparta big-power policies were associated with the harmosts, who served as magistrates in foreign areas and were not provided for in the Lycurgan system. Not mentioned in this context are the nauarchs, who served in overseas areas as ship’s captains, and could also, like the harmosts, be involved in political operations and thus win power not only for Sparta but also for themselves. In my opinion, the reasons for this silence regarding the nauarchia become evident from an analysis of the concrete actions of nauarchs in Xenophon’s Hellenika. There, as we shall see, the nauarchs are on official missions as elected magistrates, responsible to the polis, who generally worked for the strength of Sparta. Although the same persons are often involved, the nauarchs, unlike the harmosts, assumed no permanent foreign positions of rulership, which, according to Xenophon, was what was the cause of Sparta’s undoing. The nauarchs – by contrast with the harmosts – occupied individual positions, which caused fewer problems and which were not suited to maintain any permanent rulership. Therefore, Xenophon had no immediate reason to include the nauarchs in his critique of the contemporary Lakedaimonion politeia. The main thrust of his argument was rather that the role of a long-term hegemonic power in the Aegean was one that overtaxed the powers of Sparta, for the often ruthless behavior of the magistrates sent abroad was what sparked the resistance against Spartan rule. By contrast to Athens, Sparta could conduct no successful imperial policy, and only brought itself into danger. Thereby Xenophon does not take into consideration the fact that Sparta, as a land power, was dependent on a certain maritime strength and presence as well, and hence needed the right kind of commanders. Therefore, he ultimately prefers not to mention the nauarchs in connection with the ideal Spartan constitution, and to connect the city’s imperial misbehavior only with the harmosts.